Anophtalmic and epigean? Description of an intriguing new species of Hyalella (Amphipoda, Hyalellidae) from Brazil - Bastos-Pereira, Rafaela; de Oliveira, Marcus Paulo Alves; Ferreira, Rodrigo L. (Zootaxa, 2018)
The absence of eyes in Hyalella (Hyalellidae, Amphipoda) is typical of obligate groundwater-dwelling species. However, a new intriguing blind amphipod of this genus was found in epigean streams from the Iron Quadrangle (state of Minas Gerais, Brazil). Hyalella troglofugia sp nov. presents antenna 1 shorter than antenna 2, gnathopod 1 propodus inner face with four setae, gnathopod 2 propodus posterior margin longer than palm, dactylus slightly longer than palm, pereopod 5 shorter than others and uropod 3 shorter than telson. The absence of eyes and presence of reduced U3 and pereopods of H. troglofugia sp nov. may suggest that such species also inhabits interstitial subterranean spaces. Moreover, the presence of the new species on streams associated to distinct hydrological zones indicates that this species may be present in different types of subterranean habitats of the region. We hypothesize that at least part of the population of this species may have left the subterranean environment looking for food and when out of this habitat it preferentially inhabits high water flow stretches of the stream in function of predation avoidance.